Guidelines for the Management of Severe Traumatic Brain injury: 2020 update of the decompressive craniectomy recommendations (2020)
When the fourth edition of the Brain Trauma Foundation’s Guidelines for the Managementof Severe Traumatic Brain Injury were finalized in late 2016, it was known that the resultsof the RESCUEicp (Trial of Decompressive Craniectomy for Traumatic Intracranial Hyper-tension) randomized controlled trial of decompressive craniectomy would be public afterthe guidelines were released. The guideline authors decided to proceed with publi-cation but to update the decompressive craniectomy recommendations later in the spiritof “living guidelines,” whereby topics are updated more frequently, and between neweditions, when important new evidence is published. The update to the decompressivecraniectomy chapter presented here integrates the findings of the RESCUEicp study aswell as the recently published 12-mo outcome data from the DECRA (DecompressiveCraniectomy in Patients With Severe Traumatic Brain Injury) trial. Incorporation of thesepublications into the body of evidence led to the generation of 3 new level-IIA recommen-dations; a fourth previously presented level-IIA recommendation remains valid and hasbeen restated. To increase the utility of the recommendations, we added a new sectionentitledIncorporating the Evidence into Practice.This summary of expert opinion providesimportant context and addresses key issues for practitioners, which are intended to helpthe clinician utilize the available evidence and these recommendations.